Urinary Tract Infection in Children with Protein-energy Malnutrition in Aminu Kano Teaching Hospital Kano, Northwest Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Determining the antimicrobial sensitivity pattern of urinary tract infection (UTI) in malnourished children in a community will help the clinician in decision-making regarding suitable first-line antibiotics.Materials and Methods:We performed a prospective cross-sectional study from July to November 2011 at the Aminu Kano Teaching Hospital to determine the prevalence of UTI and evaluate the antibiotic sensitivity pattern of organisms isolated from the urine of children with protein-energy malnutrition (PEM) and normal controls. In total, 169 children with PEM aged 6–59 months were enrolled consecutively as subjects and 169 well-nourished age and sex-matched children as controls.Results:The prevalence of UTI was found to be 16.0% in the subjects; this was significantly higher than 2.4% in the controls. The most common isolate wasE. coliin both the subjects and controls. All isolates were sensitive to gentamycin and ciprofloxacin, whereas about half of the isolates were resistant to commonly used antibiotics such as amoxicillin, cotrimoxazole, and cefuroxime. The antibiotic sensitivity pattern of the organisms differs from other reports.Conclusion:There is high a prevalence of antibiotic resistance to the commonly used antibiotics for UTI. It is recommended that ciprofloxacin or gentamycin be considered as empirical antibiotic of choice in children with PEM and proven UTI. It is advised that regular surveillance of urinary tract pathogens should be carried out to evaluate antibiotic sensitivity pattern to guide empirical treatment.